Richard Scarry's Best sing-along Mother Goose video ever! - Scarry, Richard; Eastman, Tony; Weiss, Ellen; DeRosa, Rich (Sony Wonder Random House Home Video, 2002)
Huckle looks for his friend Lowly Worm through Mother Gooseland and meets many new friends. Sing along with classic nursery rhymes.